2011
DOI: 10.1177/1741826711401981
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular risk assessment in hypertensive patients with tests recommended by the European Guidelines on Hypertension

Abstract: With the non-routine tests, 25.4% of the low or moderate risk patients were reclassified as presenting high risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…18 These observations may be driven by the fact that subjects with previously undiagnosed hypertension already have multiple risk factors and high prevalence of target organ damage leading to subclinical atherosclerosis before the diagnosis of hypertension. We share the opinion of Go´mez-Marcos et al 19 that GFR and ABI should be included in the routine analysis of recently diagnosed hypertensive patients. For general practitioners, this allows more appropriate risk assessment and guidance to intensify treatment strategy, since target organ damage invariably place a subject with hypertension in the high-risk category.…”
Section: Discussionmentioning
confidence: 95%
“…18 These observations may be driven by the fact that subjects with previously undiagnosed hypertension already have multiple risk factors and high prevalence of target organ damage leading to subclinical atherosclerosis before the diagnosis of hypertension. We share the opinion of Go´mez-Marcos et al 19 that GFR and ABI should be included in the routine analysis of recently diagnosed hypertensive patients. For general practitioners, this allows more appropriate risk assessment and guidance to intensify treatment strategy, since target organ damage invariably place a subject with hypertension in the high-risk category.…”
Section: Discussionmentioning
confidence: 95%
“…Systematic evaluation of hypertensive patients with all the examinations recommended by the ESH/ESC guidelines is not a routine practice. Gomez‐Marcos and colleagues 20 showed that nearly 25% of low‐ and medium‐risk hypertensive patients had to be reclassified to the high‐ or very high‐risk group. Assessment of electrocardiographic left ventricular hypertrophy assessment, ABI, and estimated GFR reclassified a significant higher number of hypertensive patients to the high‐risk category as compared with Framingham risk prediction tools 21 .…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that the ankle-brachial index inversely and linearly correlates with cigarette smoking [7,8]. Nevertheless, when evaluating vascular structure and function, every test has different accessibility and costs [9]. Several authors have proposed that the patient’s age, sex, blood pressure and heart rate, and the presence of obesity, diabetes and vascular drugs, are the main determinants of the parameters that assess arterial stiffness and vascular function [10-13].…”
Section: Introductionmentioning
confidence: 99%